2003
DOI: 10.1109/mcom.2003.1179494
|View full text |Cite
|
Sign up to set email alerts
|

Optical signal processing for optical packet switching networks

Abstract: Optical packet switching promises to bring the flexibility and efficiency of the Internet to transparent optical networking with bit rates extending beyond that currently available with electronic router technologies. New optical signal processing techniques have been demonstrated that enable routing at bit rates from 10 Gb/s to beyond 40 Gb/s. In this article we review these signal processing techniques and how all-optical wavelength converter technology can be used to implement packet switching functions. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 11 publications
0
35
0
2
Order By: Relevance
“…The all-optical solution provides a much higher processing speed, provides transparency, and mitigates the optoelectronic conversion bottleneck. All-optical functions that have been developed include switching [1][2][3] header processing [4,5], buffering methods [6][7][8][9], wavelength conversion [10][11][12] signal regeneration [13], and limited signal processing used for high-speed transmission such as multiplexing and demultiplexing [14][15][16], and for logic functions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The all-optical solution provides a much higher processing speed, provides transparency, and mitigates the optoelectronic conversion bottleneck. All-optical functions that have been developed include switching [1][2][3] header processing [4,5], buffering methods [6][7][8][9], wavelength conversion [10][11][12] signal regeneration [13], and limited signal processing used for high-speed transmission such as multiplexing and demultiplexing [14][15][16], and for logic functions [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Optical burst switching (OBS) and optical packet switching (OPS) have attracted much attention in recent years, due to the potential ability to switch multi-tera bits/sec (Tbps) data in wide area networks (WAN)s with a small foot-print, low power consumption and cost [1,2]. In OBS/OPS concept, data is forwarded in the optical domain without optical-electronic-optical (OEO) conversion by an optical switch that is controlled by an attached header label before each data packet.…”
Section: Introductionmentioning
confidence: 99%
“…Many trials of ns-sized optical packet switching are reported [2], but these schemes usually require optical variable buffer memory to avoid contention, which is still an immature technology. On the other hand, optical burst switching using µs-switch and wavelength conversion for contention resolution can be a realistic solution: µs-order latency will not affect most real-time application, and scalability will be easier to simplicity of the switch and contention resolution.…”
Section: Introductionmentioning
confidence: 99%
“…High-speed all-optical switches offer advantages in power consumption, foot-print and switching architectures compared to their electronic counterparts [1]. An essential building block of an all-optical packet switch is an optical flip-flop memory that is used to store the switch decision information.…”
Section: Introductionmentioning
confidence: 99%